2018
DOI: 10.1038/s41467-018-03739-2
|View full text |Cite
|
Sign up to set email alerts
|

Constant strain accumulation rate between major earthquakes on the North Anatolian Fault

Abstract: Earthquakes are caused by the release of tectonic strain accumulated between events. Recent advances in satellite geodesy mean we can now measure this interseismic strain accumulation with a high degree of accuracy. But it remains unclear how to interpret short-term geodetic observations, measured over decades, when estimating the seismic hazard of faults accumulating strain over centuries. Here, we show that strain accumulation rates calculated from geodetic measurements around a major transform fault are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
78
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 59 publications
(70 reference statements)
9
78
1
Order By: Relevance
“…That result is consistent with previous studies (∼ 24 ± 2 mm yr −1 ) (McClusky et al, 2000;Reilinger et al, 2006;Yavasoglu et al, 2011). In addition, model locking depths and results are similar to a more recent study with InSAR, which indicates that the locking depth of the fault at theİsmetpaşa segment is around 13-17 km and longterm tectonic movement is about 24-30 mm yr −1 (Hussain et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…That result is consistent with previous studies (∼ 24 ± 2 mm yr −1 ) (McClusky et al, 2000;Reilinger et al, 2006;Yavasoglu et al, 2011). In addition, model locking depths and results are similar to a more recent study with InSAR, which indicates that the locking depth of the fault at theİsmetpaşa segment is around 13-17 km and longterm tectonic movement is about 24-30 mm yr −1 (Hussain et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…That movement does not include the whole fault plane, and thus the creeping layer seems to slip freely to 4.5 km depths from the surface and decays between 4.5 and 6.75 km. The seismic data and previous studies (Cakir et al, 2005;Yavaşoglu et al, 2011;Hussain et al, 2018) indicate that the locking depth over the fault is ∼ 15 km. This result demonstrates that the fully locked portion of the fault plane is between 6.75 and 15 km, which is supported by the χ 2 test result (1.00).…”
Section: Discussionsupporting
confidence: 53%
“…Using GPS data and additional Envisat images acquired between 2003 and 2012, from both ascending and descending orbits which allowed to better separate the horizontal and vertical components of creep, Hussain et al () reported that aseismic slip was confined to shallow depths (<10 km) and confirmed its decaying creep rate through time. Their results showed that creep extends spatially from the Gulf of Izmit in the west to the east of Sapanca Lake in the east, with an average horizontal, fault‐parallel slip rate of 6 mm/year and a maximum rate of 11 ± 2 mm/year, which is nearly 40% of the annual tectonic loading rate (Hussain et al, ; Reilinger et al, ). Such slip deficit implies that elastic strain is still being accumulated on the fault along the Izmit section.…”
Section: Introductionmentioning
confidence: 99%
“…Recent postseismic studies of great subduction zone earthquakes (e.g., the 2004 M w 9.2 Sumatra-Andaman earthquake, Wiseman et al, 2015; the 2010 M w 8.8 Maule, Chile, earthquake, Klein et al, 2016;Li et al, 2017; and the 2011 M w 9.1 Tohoku-oki, Japan, earthquake, Freed et al, 2017;Sun et al, 2014) suggest that the mantle viscosity structure is highly heterogeneous. Temporally variable viscosities have also been inferred from geodetic time series of postseismic relaxation (e.g., Freed & Burgmann, 2004;Hussain et al, 2018;Malservisi et al, 2015;Pollitz et al, 2001). Temporally variable viscosities have also been inferred from geodetic time series of postseismic relaxation (e.g., Freed & Burgmann, 2004;Hussain et al, 2018;Malservisi et al, 2015;Pollitz et al, 2001).…”
Section: Introductionmentioning
confidence: 99%